IMPACT ON THE BEHAVIOR OF SERVICE USERS IN THE CONTEXT OF INDUSTRY 4.0 - Ponomarov, Rostislav; Dligach, Andriy (Current Problems of Sustainable Development, 2026)
The article examines the impact of Industry 4.0 technologies on the behavior of service users in the context of the digital transformation of the economy. The study substantiates that the active implementation of artificial intelligence, Big Data technologies, cloud services, digital platforms, automated communication systems, and AI-driven marketing tools significantly changes the principles of interaction between businesses and consumers in the service sector. It has been determined that the development of digital business processes contributes to the transformation of traditional marketing approaches and forms a new model of customer interaction based on personalization, behavioral analytics, and digital customer experience management. Particular attention is paid to the role of artificial intelligence in modern marketing activities. The article analyzes the use of recommendation systems, predictive analytics, CRM systems, automated digital communications, and personalized advertising technologies in influencing consumer behavior. It is established that modern digital marketing is gradually shifting from mass communication to individualized behavioral influence based on the analysis of consumer data and algorithmic decision-making systems. The research demonstrates that digital technologies significantly affect the mechanisms of consumer decision-making in the service market. Modern users increasingly rely on online recommendations, digital platforms, social media communications, personalized content, and algorithmically generated information flows. As a result, consumer behavior becomes more dynamic, situational, and dependent on the quality of digital interaction with service providers. At the same time, the level of digital trust, the transparency of algorithmic systems, and the security of personal data become important factors influencing customer loyalty and consumer choices. The paper proposes a conceptual model of the impact of Industry 4.0 on service user behavior, which reflects the interconnection between digital technologies, business process transformation, AI-based marketing tools, and behavioral changes of consumers. It is proved that the implementation of AI technologies in service companies increases the effectiveness of marketing communications, improves customer experience management, and strengthens the competitive positions of businesses in the digital economy. The practical significance of the study lies in the possibility of applying the obtained results in the development of digital marketing strategies, implementation of AI-driven management systems, improvement of personalized service models, and adaptation of service business processes to the conditions of Industry 4.0.